Revisiting the secretion mechanism(s) of macrophage migration inhibitory factor—welcome to the "UPS club". Issue 9 (7th September 2020) - Hoffmann, Adrian; Bernhagen, Jürgen
Abstract : See also: Original Article by Dankers et al .